Penundaan Kehadiran Anak Akibat Perkawinan Usia Muda Ditinjau Menurut Hukum Islam (Studi pada Desa Jaling, Kecamatan Awangpone, Kabupaten. Bone) - Pranata, Wiwin; Abdul Rahim (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2018)
The aim of the study is to identify whether early marriage contributes to delaying childbirth and to identify Islamic perspective in relation delaying childbirth. As for the advantages of the research, theoretically, the results of this study are expected to contribute positively to all components of the student, so the idea of delaying childbirth due to early marriage is able to be understood. Practically, this research will be one of the reference materials for further study in wider scope. The results of the study indicated that some people perform delaying childbirth due to early marriage through their participation in Family Planning Program (KB) by injections. The incentivizing factors of their participation within the program are age and educational factor, in which the Islamic law consider this permissible only if there is an agreement between both husband and wife, it is temporary, not harmful and beneficial.